2021
DOI: 10.3390/ijms22063120
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Ranitidine Analogs as Multi-Target Directed Ligands for the Treatment of Alzheimer’s Disease

Abstract: The aggregation of amyloid β (Aβ) peptides and deposition of amyloid plaques are implicated in the pathogenesis of Alzheimer’s disease (AD). Therefore, blocking Aβ aggregation with small molecules has been proposed as one therapeutic approach for AD. In the present study, a series of ranitidine analogs containing cyclic imide isosteres were synthesized and their inhibitory activities toward Aβ aggregation were evaluated using in vitro thioflavin T assays. The structure–activity relationship revealed that the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…Recent studies have shown that BACE1 has a copper-binding site in its cytoplasmic domain and that BACE1 interacts with copper clad steel (CCS), which is an important protein that transports copper to SOD1 for activation. Because BACE1 competes with SOD1 for interaction with CCS, the up-regulation of BACE1 results in decreased SOD1 activity in cells [63,64]. Our results showed that copper up-regulated BACE1 in N2a-sw cells, and the addition of PCu significantly inhibited Cu 2+ -induced BACE1 expression and Aβ secretion.…”
Section: Pcu Inhibited Cu 2+ -Mediated Aβ Deposition In Vitromentioning
confidence: 62%
“…Recent studies have shown that BACE1 has a copper-binding site in its cytoplasmic domain and that BACE1 interacts with copper clad steel (CCS), which is an important protein that transports copper to SOD1 for activation. Because BACE1 competes with SOD1 for interaction with CCS, the up-regulation of BACE1 results in decreased SOD1 activity in cells [63,64]. Our results showed that copper up-regulated BACE1 in N2a-sw cells, and the addition of PCu significantly inhibited Cu 2+ -induced BACE1 expression and Aβ secretion.…”
Section: Pcu Inhibited Cu 2+ -Mediated Aβ Deposition In Vitromentioning
confidence: 62%